Precedent and the Aboriginal Response to Global Incursions: Smallpox and Identity Reformation Among the Coast Salish - Carlson, Keith (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2007)
AbstractAboriginal people’s responses to globalization have been varied and complex. This paper looks at one particular expression of globalism (contact-era epidemics among the Coast Salish of southwestern BC and northwestern Washington) and situates it within the context of earlier regional catastrophes as understood through legendary stories. In this way the paper reframes one of the standard interpretive paradigms of the field – that the epidemics were unprecedented and that they represented perhaps the most significant “break” in Indigenous history. The article shows the ways in which Coast Salish communities and individuals coped with disasters. It concludes that ancient stories provided people with precedents that then shaped their response to globalism. The article also illustrates the ways in which historians can learn from Indigenous modes of history, in which genealogies, myth-ages stories, and specific places play crucial roles.